The effect of facial occlusion on facial impressions of trustworthiness and dominance - Oliveira, Manuel (2022)
Recognizing the role that facial appearance plays in guiding social interactions, here we investigated how occlusions of the bottom-face region affect facial impressions of trustworthiness and dominance. Previous studies suggesting that different facial features impact inferences on these traits sustain the hypothesis that wearing a face mask will differently affect each trait inference. And specifically, that trustworthiness impressions will be more disrupted by this type of face occlusion than dominance impressions. In two studies, we addressed this possibility by occluding the bottom face region of faces that were previously shown to convey different levels of dominance and trustworthiness, and tested differences in the ability to discriminate between these trait levels across occlusion conditions. In Study 1 faces were occluded by a mask, and in Study 2 by a square image. In both studies, results showed that although facial occlusions generally reduced participants’ confidence on their trait judgments, the ability to discriminate facial trustworthiness was more strongly affected than the ability to discriminate facial dominance. Practical and theoretical implications of these findings are discussed.